State Strategic Planning Under the Drug Control and System Improvement Formula Grant Program in the United States, 1990 - Dunworth, Terence ([Verlag nicht ermittelbar], 1993)
This evaluation of the Drug Control and System Improvement Formula Grant Program focuses on the federal-state relationship and on the drug-related, crime-combat strategies that states must develop in order to receive federal aid. The primary goals of the project were to (1) describe state-established strategic planning processes, (2) evaluate the strategies, (3) report on state reactions to the program, and (4) make recommendations for improvement in strategic planning processes. Five-state, on-site observation of planning processes and a mail survey of all states and territories participating in the program were conducted, as well as a review of all strategy submissions. Variables in Part 1 include the Formula Grant Program's role in the state and its relationship with other agencies, policy boards, and working groups, the roles that these agencies play in Bureau of Justice Assistance (BJA) strategy, funds allocated to local criminal justice programs, and criteria used in selecting geographical areas of greatest need. Variables from Part 2 relate to the variety and use of state criminal justice data, difficulties in obtaining such data, federal grant requirements, allocation of subgrants, and input of various individuals and agencies in different stages of BJA strategy development.